Do arbuscular mycorrhizal fungi and organic fertilizer enhance soil properties and nutrients uptake on plant production? - Kurniawati, Ari; Agyemang, Evans Duah; Hoffmann, Sándor; Anda, Angéla; Tóth, Zoltán (Environmental and Toxicology Management, 2024)
The use of chemical ertilizer can be harmful for envionments and threaten a sustainability agriculture. One of the alternative to overcome the problem is using organic fertilizer which is eco-friendly. Another problem come when organic fertilizer cannot meet nutrients sufficiency due to low nutrients and slow-release effect. On the other hand, the use of Arbuscular Mychorrizal Fungi (AMF) has been widely used around the world to provide nutrients for plants, even allows plants to survive in severe conditions. Besides, AMF also can be used as biocontrol agen. The potential synergism between organic fertilizer and AMF is crucial to study because the effects of their combination might be positive or negative depending on environmental factors, including nutrients status in the soil and strains of AMF used. Therefore, the use of organic fertilizer and AMF combination should consider some aspects to avoid negative effects, such as unbalanced soil fertility setting and to obtain the advantages from both of them.